Ratio Legis Hak Sipil Dalam Masyarakat Hukum Adat - Novita Sari (Universitas Ekasakti, 2024)
The existence of customary law communities has been recognized in Indonesia in various policies. However, existing policies are unable to accommodate the fulfillment of the rights of indigenous peoples themselves. Discrimination against the rights of indigenous peoples often occurs, one of which is in policy making that does not involve indigenous peoples technically for the granting of Environmental Feasibility permits for Oil Palm Plantation Development Plans and Palm Oil Processing Mills for oil palm plantation companies. Ratio legis guana policy protecting the rights of indigenous peoples must accommodate the protection of the rights of indigenous peoples. So that the legal standing of indigenous peoples to obtain healthy and good environmental justice will continue to be echoed with the principles of legal standing of indigenous peoples who have special interests.